Intranasal Administration of PACAP: Uptake by Brain and Brain Region Targeting with Cyclodextrins - Nonaka, Naoko (2012)
Pituitary adenylate cyclase activating polypeptide (PACAP) is a potent neurotrophic and neuroprotectant that is transported across the blood-brain barrier in amounts sufficient to affect brain function. However, its short half-life in blood makes it difficult to administer peripherally. Here, we determined whether the radioactively labeled 38 amino acid form of PACAP can enter the brain after intranasal (i.n.) administration. Occipital cortex and striatum were the regions with the highest uptake, peaking at levels of about 2-4 percent of the injected dose per g of brain region. Inclusion of unlabeled PACAP greatly increased retention of I-PACAP by brain probably because of inhibition of the brain-to-blood efflux transporter for PACAP located at the blood-brain barrier. Sufficient amounts of PACAP could be delivered to the brain to affect function as shown by improvement of memory in aged SAMP8 mice, a model of Alzheimer’s disease. We found that each of three cyclodextrins when included in the i.n. injection produced a unique distribution pattern of I-PACAP among brain regions. As examples, β-cyclodextrin greatly increased uptake by the occipital cortex and hypothalamus, α-cyclodextrin increased uptake by the olfactory bulb and decreased uptake by the occipital cortex and striatum, and (2-hydropropyl)-β-cyclodextrin increased uptake by the thalamus and decreased uptake by the striatum. These results show that therapeutic amounts of PACAP can be delivered to the brain by intranasal administration and that cyclodextrins may be useful in the therapeutic targeting of peptides to specific brain regions.